Performance Analysis of Ejector Enhanced Multi Evaporator Cascade Refrigeration System - Shabir, Faisal (My University, 2014)
Refrigeration and air conditioning is one of the leading uses of electric power in the world. Reduction of power input to the compressor by incorporating a low grade heat operated pre compression device is one of the efficient ways to reduce fossil fuel consumption and thereby reduce the environmental hazards. In the present study, an improved cooling cycle for multi evaporator cascade refrigeration system enhanced by incorporation of ejectors for pre compression of refrigerant vapour is analyzed. The ejector enhanced multi evaporator cascade refrigeration system (EEMECRS) consists of two stages; the lower stage has three evaporators to achieve low temperature cooling at different temperatures , the upper stage has two evaporators, one for air conditioning purposes, and other to absorb heat rejected from the lower stage. The two stages are interconnected through an intercooler which acts as a condenser to the lower stage and one of the evaporators for the upper stage. A mathematical model based on mass and energy conservation in each component is developed to analyze the performance of EEMECRS. For ejector, one dimensional mathematical model previously developed by Kairouaniet al.(2009) for constant area ejector flow is modified to account for the losses in primary nozzle and so that it could be applied to EEMECRS operating with several working refrigerants. Four refrigerants in each stage of EEMECRS giving a total of sixteen combinations of refrigerants in upper and lower stage of EEMECRS were analyzed to identify the pair of refrigerants which give best performance. R1270 and R142b in lower and upper stage of EEMECRS respectively were found to give best performance. The novel system has been theoretically investigated for various performance characteristics. The comparison between novel and unenhanced multi evaporator cascade refrigeration system (UMECRS) has been made under same operating conditions. EEMECRS is developed keeping in view needs of medical industry where medicines are required to be cooled at different low temperatures and also requires air conditioning for working spaces of employees. The results show that COP is improved by 28% for best refrigerant pair i.eR1270 in lower stage and R142b in upper stage of EEMECRS.
ME-Thermal Engineering-Thesis
Keywords: Ejector; Cascade Systems; Multi-evaporator Systems; Hybrid Systems; MED; Mechanical engineering